2021
DOI: 10.1088/1402-4896/ac2eca
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Fisher information and skew information correlations in dipolar spin system

Abstract: Quantum Fisher information (QFI) and skew information (SI) plays a key role in the quantum resource theory. Understanding these measures in the physical system has practical significance in the state parameter estimation and quantum metrology. In this article, we consider a pair of spin-1/2 particles coupled with dipolar and Dzyaloshinsky-Moriya (DM) interactions, serving as the physical carrier of quantum information. We examine the bipartite nonlocal correlations of pair of spin-1/2 particle system for the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, we observe that the increasing of the energy parameter ϵ leads to a rapidly decay of the quantum correlation due to the factor exp − 1 2 γtϵ 2 and decreases therefore the oscillations numbers. Nevertheless, it was shown that the parameter ϵ strengthen quantum resources if we immerse the system in the thermal bath [44]. Further, we also notice that the another energy parameter ∆ and DM interaction do not affect the any quantum correlation measures.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, we observe that the increasing of the energy parameter ϵ leads to a rapidly decay of the quantum correlation due to the factor exp − 1 2 γtϵ 2 and decreases therefore the oscillations numbers. Nevertheless, it was shown that the parameter ϵ strengthen quantum resources if we immerse the system in the thermal bath [44]. Further, we also notice that the another energy parameter ∆ and DM interaction do not affect the any quantum correlation measures.…”
Section: Resultsmentioning
confidence: 63%
“…In order to examine the behaviour of quantum correlations dynamics in a physical system under the intrinsic decoherence effects, we consider the two-spin-1/2 particles coupled with dipolar and DM interactions described by the following Hamiltonian [43][44][45][46]…”
Section: Dipolar Spin System and Initial Statementioning
confidence: 99%
“…Among these are Heisenberg exchange, which is isotropic under rotations in spin space [4,6,20,21], and Dzyaloshinskii-Moriya (DM) interaction [32][33][34], which accounts for weak ferromagnetism in some antiferromagnetic materials [12]. A ubiquitous example of anisotropic coupling in LDMCs is the dipolar interaction [17,[27][28][29][30][31]. This coupling arises from the influence of a magnetic field yielded by one of the magnetic moments in the other ones [12].…”
Section: Dinuclear Metal Complex With Dipolar Interactionmentioning
confidence: 99%
“…Therefore, from Eqs. ( 5), ( 20) and (31), one can obtain the analytical expressions for the normalized axial quantum coherences as…”
Section: A Axial Coherencementioning
confidence: 99%
See 1 more Smart Citation